2009
DOI: 10.1111/j.1540-8183.2009.00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Quantification of Thrombus in ST‐Elevation Acute Myocardial Infarction Presenting with an Occluded Infarct‐Related Artery and Its Relationship with Results of Percutaneous Intervention

Abstract: Only a third of STEMI patients present with an LT, being diabetes and lack of clopidogrel pretreatment independent predictors. An LT is strongly associated with worse PCI results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Those which did not provide these features angiographically were defined as grade 0, 1, 2, 3. Finally, we classified patients as a high thrombus burden (grade 4 and 5) and low thrombus burden (grade 0, 1, 2, 3) in our study 17) .…”
Section: Methodsmentioning
confidence: 99%
“…Those which did not provide these features angiographically were defined as grade 0, 1, 2, 3. Finally, we classified patients as a high thrombus burden (grade 4 and 5) and low thrombus burden (grade 0, 1, 2, 3) in our study 17) .…”
Section: Methodsmentioning
confidence: 99%
“…As reported previously in de novo lesion STEMI, a high thrombus grade is more often seen with reduced initial TIMI 3 flow and the same finding was observed in this study with ST. Glycoprotein IIb/IIIa inhibitors were administered more often to patients with high thrombus burden, likely due to operator recognition of the requirement for potent and immediate antiplatelet therapy. A large thrombus burden during de novo STEMI treated with PCI is associated with an increased risk of future ST and correlates with worse outcomes . A high thrombus grade during PCI for ST was also previously reported to be associated with recurrent ST .…”
Section: Discussionmentioning
confidence: 77%
“…Although proximal location of culprit lesion was higher in OC (+) group, it is unrelated to thrombus grade. Miranda‐Guardiola et al also showed that there is no predictive role for the location of the culprit lesion on the thrombus grade. Thrombus containing lesions are well‐known predictors of complications in P‐PCI because of increased risk of acute vessel closure, no reflow, distal embolization, reinfarction, and stent thrombosis.…”
Section: Discussionmentioning
confidence: 99%